Administrative decision-making in Australian migration law - Freckelton, Alan (ANU Press, 2015)
The ANU College of Law, Migration Law Program is pleased to introduce a text in administrative decision-making in Australian migration law. Over the past eight years we have assembled a team of some of Australia's most highly qualified migration agents and migration law specialists to deliver the Graduate Certificate in Australian Migration Law & Practice, and the Master of Laws in Migration Law. Alan Freckelton has worked with the Migration Law Program since 2008. Through personal recollections and a comprehensive analysis of administrative decision-making, he brings his professional expertise and experience in this complex field of law to the fore. The examination of High Court decisions, parliamentary speeches and public opinion bring a contentious area of law and policy to life, enabling the reader to consider the impact that legislation and decision-making has upon the individual and society as a whole.